A novel double kink-turn module in euryarchaeal RNase P RNAs - Lai, Lien B. (Nucleic Acids Res, 2017)
RNase P is primarily responsible for the 5΄ maturation of transfer RNAs (tRNAs) in all domains of life. Archaeal RNase P is a ribonucleoprotein made up of one catalytic RNA and five protein cofactors including L7Ae, which is known to bind the kink-turn (K-turn), an RNA structural element that causes axial bending. However, the number and location of K-turns in archaeal RNase P RNAs (RPRs) are unclear. As part of an integrated approach, we used native mass spectrometry to assess the number of L7Ae copies that bound the RPR and site-specific hydroxyl radical-mediated footprinting to localize the K-turns. Mutagenesis of each of the putative K-turns singly or in combination decreased the number of bound L7Ae copies, and either eliminated or changed the L7Ae footprint on the mutant RPRs. In addition, our results support an unprecedented ‘double K-turn’ module in type A and type M archaeal RPR variants.